Establishing Hematopoietic Stem Cell Transplant Unit in Resource Limited Setting: A Critical Analysis of Indian Council of Medical Research 2017 Guidelines - Kunal Das; Tanvi Khanna; Nitika Agrawal (Journal of Transplantation)
The scope and application of hematopoietic stem cell transplantation are increasing. With advancement in science and close cooperation of health centers, HSCT units are coming up in new developing and underdeveloped countries. India hosts many HSCT units and often provides financially viable option for HSCT to foreign patients as well. Recently Indian Council of Medical Research (ICMR) issued a guideline about HSCT unit in India. This review article discusses establishment of new HSCT unit in resource limited setting. Subsequent implication of ICMR guideline has been done.